UNESCO KONFERANSI HAKKINDA NOTLAR: WORLD HERITAGE AND CONTEMPORARY ARCHITECTURE-MANAGING THE HISTORIC ENVIRONMENT VIYANA, MAYIS 2005 - Turkyilmaz, Cigdem Canbay; Turkyilmaz, Emrah (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2006)
Out of the 780 World Heritage Sites currently on UNESCO's World Heritage List, 300 are cities, urban centre or monuments located within an urban context. All of these properties have been identified as being of outstanding universal value to the international community, and it is the responsibility of the international community to cooperate in their protection. This paper is prepared to inform Turkish architectural community about the International Conference: World Heritage and Contemporary Architecture-Managing the Historic Environment and to emphasize the protection and management of the historic urban landscapes once more.
Keywords: UNESCO; World Heritage; Vienna Memorandum; historic urban landscapes; Architecture